Analisis Perlindungan Hukum Terhadap Nasabah Korban Kejahatan Penggandaan Kartu ATM Pada BCA Kantor Cabang Pembantu Penuin Batam - Lendrawati Lendrawati; David David (Fakultas Hukum, Universitas Internasional Batam, 2019)
This research was carried out by researcher starting from the skimming cases that occurred among banks in Indonesia, one of them in BCA, especially BCA Penuin Sub Branch Office, Batam City. This study aims to explain the procedures for handling victims of ATM card duplication crimes and analyze what legal protection can be received by customers who are victims of ATM card duplication at the BCA Penuin Sub Branch Office. Researcher used normative juridical legal research methodology with using secondary data, among others, obtained from literature studies and interviews. After all data is collected, then the data is then filtered and analyzed, the analysis is used qualitatively by classifying the aspects studied. Then conclusions are drawn relating to this research and described descriptively. Based on this research, the results were reviewed by the researcher from 2 (two)formulation of the problem. Research is expected to be useful to provide insight for all people in Indonesia.